gem-Difluoromethylation of α- and γ-ketoesters: preparation of gem-difluorinated α-hydroxyesters and γ-butyrolactones - Manat Pohmakotr (2018)
PhSCF2SiMe3has been demonstrated as difluoromethyl carbanion synthon (-CF2H). It reacts chemoselectively with α- and γ-ketoesters at the keto group in the presence of a catalytic amount of TBAF in THF to give the corresponding α-hydroxy ester adducts as well as γ-gem-difluorophenylsulfanylmethylated-γ-butyrolactones in good yields. Reductive cleavage of the phenylsulfanyl group of these products employing Bu3SnH/AIBN gives the corresponding gem-difluoromethylated α-hydroxyesters and γ-butyrolactones in good yields. © 2007 Elsevier Ltd. All rights reserved.